The effect of different degrees of lockdown and self-identified gender on anxiety, depression and suicidality during the COVID-19 pandemic: Data from the international COMET-G study. (September 2022) - Fountoulakis, Konstantinos N.; Karakatsoulis, Grigorios N.; Abraham, Seri; Adorjan, Kristina; Ahmed, Helal Uddin; Alarcón, Renato D.; Arai, Kiyomi; Auwal, Sani Salihu; Berk, Michael; Bjedov, Sarah; Bobes, Julio; Bobes-Bascaran, Teresa; et al.
Highlights: COVID-19. Depression. Suicidality. Lockdown. Anxiety. Abstract: Introduction: During the COVID-19 pandemic various degrees of lockdown were applied by countries around the world. It is considered that such measures have an adverse effect on mental health but the relationship of measure intensity with the mental health effect has not been thoroughly studied. Here we report data from the larger COMET-G study pertaining to this question. Material and Methods: During the COVID-19 pandemic, data were gathered with an online questionnaire from 55, 589 participants from 40 countries (64.85% females aged 35.80 ± 13.61; 34.05% males aged 34.90±13.29 and 1.10% other aged 31.64±13.15). Anxiety was measured with the STAI, depression with the CES-D and suicidality with the RASS. Distress and probable depression were identified with the use of a previously developed cut-off and algorithm respectively. Statistical Analysis: It included the calculation of Relative Risk (RR), Factorial ANOVA and Multiple backwards stepwise linear regression analysis Results: Approximately two-thirds were currently living under significant restrictions due to lockdown. For both males and females the risk to develop clinical depression correlated significantly with each and every level of increasing lockdown degree (RR 1.72 and 1.90 respectively). The combined lockdown and psychiatric history increased RR to 6.88 The overall relationship of lockdown with severity of depression, though significant was small. Conclusions: The current study is the first which reports an almost linear relationship between lockdown degree and effect in mental health. Our findings, support previous suggestions concerning the need for a proactive targeted intervention to protect mental health more specifically in vulnerable groups